Muscle shear elastic modulus measured using supersonic shear imaging is highly related to muscle activity level - Nordez, Antoine; Hug, François (Journal of applied physiology (1985), 2010)
This pilot study was designed to determine whether the shear elastic modulus measured using supersonic shear imaging can be used to accurately estimate muscle activity level. Using direct visual feedback of torque, six healthy subjects were asked to perform two incremental isometric elbow flexions, consisting of linear torque ramps of 30 s from 0 to 40% of maximal voluntary contraction. Both electromyographic (EMG) activity and shear elastic modulus were continuously measured in the biceps brachii during the two ramps. There was significant linear regression ( P < 0.001) between shear elastic modulus and EMG activity level for both ramps of all six subjects ( R 2 = 0.94 ± 0.05, ranging from 0.82 to 0.98). Good repeatability was found for shear elastic modulus estimated at both 3% ( trial 1: 21.7 ± 6.7 kPa; trial 2: 23.2 ± 7.2 kPa, intraclass correlation coefficient = 0.89, standard error in measurement = 2.3 kPa, coefficient of variation = 12.7%) and 7% ( trial 1: 42.6 ± 14.1 kPa; trial 2: 44.8 ± 15.8 kPa, intraclass correlation coefficient = 0.94, standard error in measurement = 3.7 kPa, coefficient of variation = 7.1%) of maximal EMG activity. The shear elastic modulus estimated at both 3 and 7% of maximal EMG activity was not significantly different ( P > 0.05) between the two trials. These results confirm our hypothesis that the use of supersonic shear imaging greatly improves the correlation between muscle shear elastic modulus and EMG activity level. Due to the nonlinearity of muscle mechanical properties, the muscle elasticity should be linked to the muscle stress. Therefore, the present study represents a first step in attempting to show that supersonic shear imaging can be used to indirectly estimate muscle stress.